Pengaruh Green Human Resource Management dan Green Behavior terhadap Green Employee Performance pada Industri Fast Food di Kabupaten Garut - Rini Siti Nurlaeli; Rohimat Nurhasan; Wufron (POLITEKNIK LP3I, 2026)
The researchers in this study set out to find out how well fast food workers in Garut Regency practice green HRM and environmentally conscious behavior. This study is motivated by the increasing environmental issues caused by the fast food industry, including food waste, plastic waste, and excessive energy use. In this quantitative study, 75 participants were chosen for the survey using a purposeful selection technique. The data was evaluated using multiple linear regression in SPSS. To back up the results, validity, reliability, and standard assumption tests were utilized. The results show that GHRM has a positive and significant effect on GEP (β = 0.081; p < 0.05), whereas GB has a larger influence (β = 0.276; p < 0.05). The combined effect of the two variables on GEP was substantial, with an adjusted R-squared value of 0.726. In addition to company policy, these findings demonstrate that employee behavior affects environmental performance. Businesses may do their part to encourage eco-friendly practices by bolstering waste management education, garbage sorting infrastructure, and environmental rewards.